Effect of chitosan nanoparticles conjugated with the cell free supernatant of Bifidobacterium bifidum on the expression of genes related to colorectal cancer in colon adenocarcinoma (Caco-2) cell line - Rahimeh Maqsoodi; Masoumeh Saberpour; Bita Bakhshi; Fatemeh Fallah (BMC Gastroenterology)
Abstract Background Colorectal cancer (CRC) is emerged as a global problem with high mortality rate; hence, finding of alternative treatment approaches is essential. The purposes of this research are to assess the impact of chitosan nanoparticles conjugated with the cell free supernatant of Bifidobacterium bifidum (CTNP/B.b-sup) on genes associated with CRC signaling pathways. Methods The novel nano-drug were fabricated via an ionic gelation technique and analyzed using transmission electron microscopy (TEM) and dynamic light scattering (DLS) methods. The release of protein and entrapment efficiency (EE) of CTNP/B.b-sup were assessed using a BCA protein assay. Following an investigation into the toxicity of CTNP/B.b-sup on Caco-2 cells by MTT assay, the expression of genes associated with CRC signaling pathways was evaluated utilizing real-time PCR method. Results CTNP/B.b-sup exhibited a suitable morphology with a particle size of 453.1 ± 230.8 nm and zeta potential of 9.11 ± 3.6 mV. The protein released was 75.5% at pH ~ 6.8 within 48 h with 83.3% of EE. The viability of Caco-2 cells against CTNP/B.b-sup was 90.3%. The effects of CTNP/B.b-sup on the expression levels of various oncogenes reveal a significant decrease in the expression of β-Catenin, PI3K, TGF-α, Bcl2, TLR4, CEA, and TGF-β oncogenes by 0.96, 0.37, 0.03, 0.41, 0.88, 0.69, and 0.71-fold, respectively. CTNP/B.b-sup induced the most significant reduction in TGF-α oncogene expression, with a decrease of 0.03-fold. Conversely, the strongest induction was observed in the expression of Caspase9 suppressor, with a 73.4-fold increase. Conclusion In the present study, the CTNP/B.b-sup was demonstrated to possess the capability of modulating genes associated with CRC progression, thereby highlighting its significant pro-apoptotic potential. It can be concluded that CTNP/B.b-sup is a suitable drug delivery system with anticancer properties, which can be regarded as a complementary therapeutic approach for the treatment of CRC.